(untitled) (Prithvi Academic Journal, 2018)
Human beings have been very protective about their identities. Cultural identity is one of the mechanisms that keep them connected to each other and their roots in the globalized world. This becomes more evident in times of threat and uncertainty about their belonging. Therefore, the issues of identity come to the fore in migration and diaspora discourses. In this article, I draw from Stuart Hall’s idea of identity and argue that irrespective of the socio-cultural disorientation and ethnic prejudices, in which the central character undergoes in the novel and craves for and succeeds in creating an identity. Not only the protagonist but also other characters come together to proclaim their identity which on the other hand establishes Atlantic Street as a novel by Rajab1 that represents ethnic prejudices. However, the prejudices the characters suffer, in turn, help to bring together the characters who suffer and constitute an ethnic bond between them. The inscription of the lack of recognition as human beings, and the pursuit of identity in and through literature respectively, reiterate the fact that both literature and identity are cultural products that are entwined.